Pattern of Bacteria, Antibiotic Uses and Sensitivity among Ear, Nose, and Throat Infectious Disease in Otolaryngology Ward in Tertiary Hospital - Yolla Sri Agustina; Imam Megantara; Arif Dermawan (International Journal of Integrated Health Sciences, 2019)
Objective: To provide an overview of antibiotic use, bacterial patterns and sensitivity to antibiotics in the otolaryngology ward.Methods: This was a cross-sectional study, with total sampling method from medical record data of otolaryngology inpatients that use antibiotics for the period of January 1, 2016–June 30, 2016. Exclusion criteria are incomplete patient medical records and chemotherapy or radiotherapy patients. The variables studied were antibiotic use, bacterial pattern and susceptibility.Results: Among 276 subjects included in the inclusion criteria, the most widely used are single antibiotics (98.9%), generally used for 2–3 days (73.9%), via intravenous lines (92%), and with indications as empirical+prophylaxis (77.5%). Commonly used antibiotics are cefazolin (42.51%), ceftriaxone (29.54%), and cefotaxime (20.76%). The most common bacteria were E. coli (36.36%) and the most sensitive types of antibiotics were meropenem, amikacin, and tigecyclin, while the most resistant antibiotics were ampicillin, ciprofloxacin, and ceftriaxone.Conclusions: The majority of antibiotics used in the otolaryngology treatment room are cefazolin as prophylaxis. E. coli were the most found culture results and the most sensitive types of antibiotics, namely meropenem, amikacin, and tigecyclin, while the most resistant antibiotics were ampicillin, ciprofloxacin, and ceftriaxone.Keywords: Antibiotics, antibiotic sensitivity, bacterial pattern, ears, nose, throat